Engineering Properties of High Strength Blended Concrete Enhanced with Nano POFA. (April 2019) - Wan Hassan, W N F; Ismail, M A; Lee, H S; Hussin, M W; Ismail, M
Abstract: Global demand for cement in construction industry is expected to increase to 400% by year 2050 hence, contributes to the increasing global CO2 emission. One of the alternative options that considered realistic to reduce usage of cement is using the blended concrete which replacing cement with other waste materials that contain cementitious properties. In this study, the engineering properties of high strength blended concrete such as workability, compressive, splitting tensile and flexural strengths were investigated. To achieve the aim, a total of 126 concrete specimens were produced that consist of concrete cubes, cylinders and prisms. Ten different mixes of blended concrete with the cement replacement of 0 to 30% of the 45-micron size of POFA and 1-3% of nano POFA. The hardened properties of blended concrete were determined at the age of 7, 28 and 90 days. The findings revealed that, the enhancement of the 2-3% of nano POFA improved the concrete workability with 5 to 10 mm increment of slump height. At all age of curing, the blended concrete consists of 10% of micro POFA and 1 to 3% of nano POFA showed a higher strength compared with the plain concrete. The highest enhancement strength of compressive, splitting tensile and flexural were 4%, 10% and 11% respectively at certain age of curing. These results showed the improvement of the engineering properties of the blended concrete with enhancement of the nano POFA.